Eosinophilic Esophagitis: An Increasingly Recognized Disease in Recent Era - Khalil, Md Musab; Patwary, Md Rezaul Islam; Miah, Md Rubel; Shapla, Mahfuza Akhter; Ahmed, Faruque; Islam, Md Ashraful; Hossain, Mohammad Iqbal (Journal of Medicine, 2019)
Eosinophilic esophagitis (EoE) is characterized by eosinophilic infiltration of the esophagus. It has become increasingly recognized over the last decade. It is associated with a variety of esophageal symptoms such as dysphagia, food impaction and chest pain. Diagnosis of the disorder is dependent on the patient’s clinical presentation and histological findings on esophageal mucosal biopsies. Eosinophilic esophagitis (EoE) is being recognized increasingly all over the globe; however Bangladeshi data on eosinophilic esophagitis is sparse and no case report has so far been made. In our this case report a 14-year-old boy presenting with dysphagia for last few years with weight loss was diagnosed as eosinophilic esophagitis after biopsy from esophageal stricture and ulceration. He was managed initially with enodoscopic dilatation followed by steroids & improved clinically. J MEDICINE JUL 2019; 20 (2) : 109-111